Tourist Preferences in Visiting Marine Tourism Attractions in Makassar City: Case Study on Akkarena Beach, Makassar City - Zahra, Raden Ajeng Azmi Hayatunufus Fajri; Kamaruddin, Citra Ayni; Jamil, Muh.; Samsir, Andi; Hastuti, Diah Retno Dwi (Newinera Publisher, 2024)
Tourism directly provides employment opportunities for the community, reduces poverty and unemployment levels, creates new business opportunities, increases regional income, and increases national foreign exchange earnings. The presence of tourism can generate commercial activities that can bring significant social, cultural and economic benefits to the country. This research aims to determine tourists' preferences in visiting the marine tourism attraction Akcepatn Beach, Makassar City. The type of research used is descriptive research using qualitative research methods. The research location was carried out at Akbecause Beach which is located on Jl. Tanjung Merdeka, Tamalate District, Makassar City. The population used in this research were tourists who had visited Akcepatn Beach, Makassar City. The method for determining the sample in this research is using accidental sampling. Data collection was carried out through interviews, observation and documentation with data analysis used namely data exploration, data reduction, data presentation and drawing conclusions. The research results show that the tourist attractions offered are the main factor for tourists in determining their preferences when visiting Akcaus Beach, Makassar City. Meanwhile, the price indicator is not a choice for tourists to come to visit. Meanwhile, facilities and accessibility also play an important role in determining tourists' preferences in visiting Akcaus Beach.